2013
DOI: 10.1186/1477-7525-11-187
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity and quality of life outcomes in adults with severe obesity: a cross-sectional study prior to the beginning of a lifestyle intervention

Abstract: BackgroundSeverely obese individuals who seek lifestyle interventions have impaired quality of life (QoL). Research suggests that physical activity (PA) plays a role in weight reduction and improved health in this group, but knowledge about the association of PA with QoL outcomes is sparse and inconsistent. The aim of this study was to investigate whether a higher level of PA was independently associated with higher QoL in severely obese individuals prior to the beginning of a lifestyle intervention.MethodsDur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
1
14
1
2
Order By: Relevance
“…This improves the overall quality of life [20, 21]. Similar results were found in special populations such as the elderly or the obese [22, 23]. …”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…This improves the overall quality of life [20, 21]. Similar results were found in special populations such as the elderly or the obese [22, 23]. …”
Section: Introductionmentioning
confidence: 53%
“…Similarly, the comprehensive review of Vagetti et al [44] indicated a positive association between physical activity and quality of life in the elderly that was consistently associated with functional ability and vitality, among other domains. A cross-sectional study of adults with obesity conducted by Jepsen et al [23] prior to a lifestyle intervention showed a significant association with general health. In contrast, a randomized controlled clinical trial of inactive persons [16] with a program to promote physical activity as an intervention, found no statistically significant changes between the experimental and control group in regard to the quality of life related to health.…”
Section: Discussionmentioning
confidence: 99%
“…La obesidad y el sobrepeso son considerados hoy en día enfermedades crónicas de origen multifactorial prevenibles, caracterizadas por una acumulación excesiva de grasa o hipertrofia general del tejido adiposo en el cuerpo (1). Una elevada cantidad de adiposidad central y visceral se encuentra asociada a elevado riesgo cardiovascular, aumentando la síntesis de colesterol, glucosa e insulina, generando alteraciones metabólicas (2).…”
Section: Introductionunclassified
“…(17) encontraron un aumento de precursores de la biogénesis mitocondrial (PGC-1α) 24 y 48 horas después de la administración de O3 a células de rabdomiosarcoma humano. Estos resultados sugieren que los aumentos de VO 2max reportados posterior a suplementación de O3 se deberían al incremento en precursores de la biogéne-sis mitocondrial y aumentando la capacidad oxidativa total del músculo esquelético (1). Sin embargo, la combinación de HIIT y suplementación de O3 no han sido investigados; es posible que la combinación de estas dos intervenciones combinadas produzca mejores adaptaciones metabólicas que cada una por separado.…”
Section: Introductionunclassified
“…In combination with diet modification, physical activity (PA) constitutes a core component of many lifestyle interventions for severely obese adults (Kirk et al, 2012;Dalle Grave, Calugi & El Ghoch, 2013). Studies have shown that PA impacts on weight loss and its maintenance (Catenacci & Wyatt, 2007;Butryn, Webb & Wadden, 2011), improves body composition (Lee et al, 2005;Kay & Fiatarone Singh, 2006;Goodpaster et al, 2010), reduces risk of cardio-metabolic comorbidities (Fogelholm, 2010;Goodpaster et al, 2010), and is positively associated with quality of life (Bond et al, 2006;Lerdal et al, 2011;Jepsen et al, 2013) in severely obese subjects. Thus, given the chronic nature of severe obesity, adherence to PA is important (Tsigos et al, 2008), but unfortunately PA decreases with increasing body mass index (BMI) (Tudor-Locke PeerJ reviewing PDF | (v2014:05:2118:1:1:NEW 1 Jul 2014) et al, 2010;Hansen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%